Como as técnicas determinam o futuro? : ciência do destino e destinos da ciência em Fundação de Isaac Asimov (1940-1960) - Bonfim, Luis Claudio dos Santos (2021)
This thesis presents an interpretation of psychohistory and its positivity in the works that compose the Isaac Asimov’s trilogy Foundation, that were published between 1940-1950. Following the movements of fictional figure that centralizes the plot, this fictional science that has a series of objective attributes – mathematical, sociological and psychological, neurological – that are opposed to another set of subjective attributes – wills and interests, languages, organic evolution and consciousness - we look for a positive meaning that for Asimov defined scientific rationality and human destiny. The purpose of this approach is to comprehend how Asimov and the Hard Science Fiction he represented, shaped a positive destiny in the 1950s. What identified and contrasted this positive destiny. And from this shape what fit in or what did not fit in the positive meaning that unfolded from the conceptions of objectivity, technique and formal operability. This reading take us to a critical moment of science objectivity question, shrouded by its epistemological questions in the years between 1940-1960. And for which Foundation sought to give an answer, continuing, in the terms of the 1950s, a purely objective signification project for man that was initiated on the threshold of modernity (18th and 19th centuries).